Edukasi Aktifitas Fisik Pada Ibu Hamil Di Kecamatan Gonila Dengan Media Power Point - Tiara Fatmarizka; Ayundya Putri; Nadiya Izzatul Jannah; Kusumandari Nur Shafana; Nadya Fitri Kirana; Devina Putri Yunardi; Arif Pristianto (Jurnal Pengabdian Masyarakat, 2023)
Pregnancy is a unique event for women that can cause physical and physiological changes. Therefore, it is important for pregnant women to be educated about the importance of exercising regularly so that they can live a healthy and happy pregnancy. The importance of physical activity for pregnant women to maintain health and fitness. The research was conducted through counseling to 10 pregnant women using pre-test and post-test. The results show that before counseling, the majority of pregnant women still did not fully understand the physical activities that could be done during pregnancy. However, after counseling, all participants managed to understand and were able to apply physical activity well. The conclusion of this research is the need for more intensive and targeted educational efforts to increase pregnant women's understanding of the benefits of physical activity during pregnancy.